Rede de cuidado em saúde mental em uma região de saúde do Paraná - Makiyama, Marcia (2019)
Introduction: The mental health network must be organized in order to offer care and promote comprehensive care for users in mental suffering. In this sense, the professional's performance can favor the guarantee of these rights; therefore, public policies and financing, combined with a robust health system, trained professionals, guidelines, flows and points agreed with defined responsibilities, are proposed for the integration of mental health in Primary Care. Thus, the general objective of this work was to analyze the organization of the mental health care network in 24 municipalities in the 10th Regional Health Region of Paraná regarding specific objectives, aimed at understanding the structure and organization of the health network, the flow and mental health practices and understanding the perception of professionals in relation to the mental health care network in the 24 municipalities of the 10th Regional Health Region of Paraná. Methodology: This is exploratory field research, with an approach to quantitative aspects. Data collection was carried out from February to May 2019, through the application of a semi-structured questionnaire to professionals who serve mental health users in the 24 municipalities that authorized the research, and an interview with a technician from the Tenth Health Region Paraná, in order to complement the quantitative data. Results and discussion: The professional profile revealed a female prevalence, (92%), n = 22, age between 30 to 35 years, (29%), n = 7, Psychology degree, (54%), n = 13 , and working time between 1 to 3 years (50%), n = 12, ahead of health services. The diverse socioeconomic, cultural and demographic conditions of the 24 municipalities studied define the structure of mental health care services and influence health practices, with all (100%), n = 24, having at least one Strategy unit. Family Health, and (17%), n = 4, do not have a Family Health Support Center. Health service practices reveal that (42%), n = 10, perform risk stratification, (67%), n = 16, claim to provide mental health care according to the parameters of the Psychosocial Care Network, of which, (54%), n = 13, confirm formal or informal communication with other services. The professionals answered that they perform Therapeutic Accompaniment (TA), (100%), n = 24; however, they do not recognize qualified listening and embracement as essential for the bond and the main complaint of the user's handling difficulties. Final considerations: The heterogeneity regarding the frequency of meetings and the way professionals communicate with other services is perceived. The study allowed the visualization of health gaps, gaps in the practices of the work process and the need for training professionals. It is understood that the study can contribute to the strengthening of public policies and mental health practices.